Distribuição da biomassa e minerais em família de bananeira 'Prata-Anã' adubada com zinco via broto desbastado - Rodrigues, Maria Geralda Vilela; Pacheco, Dilermando Dourado; Natale, William [UNESP]; da Silva, José Tadeu Alves; Dias, Mário Sérgio Carvalho (My University, 2010)
In the North of Minas Gerais it is cultivated basically 'Prata-Anã' banana, a cultivar that requires mainly Zn. The possibility of zinc supply, without this nutrient getting in contact with the soil, it is important for the region, since several factors take to the low availability of the element supplied by the soil, as: elevated organic matter content on the surface (from cultural residues); maintenance of high pH of the soil - above 6,00 - as strategy contrary to the proliferation of the causal agent of the Fusarium Wilt; frequent fertilizations with potassium and magnesium that, besides converting the medium into base, they reduce the participation of Zn in the balance cation/anion of the soil, hindering the absortion of this micronutrient by the plant. For determining the distribution of biomass and minerals in the 'Prata-Anã' banana, cultivated under irrigation in the North of Minas Gerais, when the zinc was supplied through thinned sprout, an experiment was carried out in the Irrigated Perimeter of Jaíba. The plants were fertilized with 0,00; 1,66 and 3,33 g.family-1 of Zn, through thinned sprout. One month after the fertilizations from October 2007 and February 2008, the production of fresh mass (FM) and dry mass (DM) were evaluated, the contents and meanings of minerals in all the bananas family bodies composed by mother-plant with bunch + tall daughter-plant + granddaughter-plant. The doses of Zn did not influence on the production of FM and DM of the plants in the first evaluation, while in the second evaluation positive effect of the treatment was observed just for MF accumulated in the inferior leaves, in the portions of the medium third and inferior of the pseudostem, and in the mother-plant's rhizome. As much the content as the accumulation of nutrients in the mother-plants presented the following decreasing order: K > N > Ca > Mg > P > S > Fe > Zn > B > Cu. The Zn contents were affected by the dose of that micronutrient in the most of the studied situations. The zinc supplied through thinned sprout increased in the mother-plant, and then it was redistributed in the banana's family.
Biomass and minerals distribution in family of banana 'Prata-Anã' fertilized with zinc through thinned sprout
Keywords: Fertilization; Micronutrient; Musa sp; Plants nutrition